SHORT-VIDEO-BASED ECO-PEDAGOGY: THE EFFECTIVENESS OF DIGITAL CONTENT IN CULTIVATING ECOLOGICAL AWARENESS AMONG GENERATION ALPHA IN ISLAMIC SCHOOLS - Khotijah Ulfa Bin Yahya; Rika Sartika (International Journal of Multidisciplinary Reseach, 2026)
Generation Alpha refers to the cohort born from 2010 to the present, the first generation to grow and develop entirely within a digital ecosystem, where technology and visual content have become an inseparable part of their daily lives. Unlike previous generations, this group has a shorter attention span, processes information more quickly through moving media, and tends to disregard static and lengthy delivery methods (Pratama : 2025). At the same time, the increasingly urgent environmental crisis demands educational efforts capable of instilling ecological awareness from an early age. For Islamic schools, environmental preservation is not merely a humanitarian responsibility, but a noble mandate of humans as khalifah fil ardh (vicegerents on earth) entrusted by Allah SWT to maintain the balance of all His creations (Al-Qur’an Surah Al-Baqarah [2]: 30). However, field realities show that learning in both Islamic Religious Education (PAI) and environmental studies still largely relies on lecture methods and textbooks, which often fail to accommodate the distinct learning styles of this generation. This study aims to analyze the relevance, conceptual foundations, and effectiveness of the short-video-based eco-pedagogy approach in fostering ecological awareness rooted in Islamic values among Generation Alpha students. The study employs a library research method by reviewing various relevant scientific literature published between 2020 and 2026. The findings reveal that short-form videos of 15–60 seconds are able to bridge the gap between teaching materials and students’ preferences, so that messages on environmental preservation linked with verses from the Al-Qur’an and Hadith can be received more deeply rather than remaining as superficial knowledge (Gunawan : 2024). Furthermore, this approach has proven to significantly enhance learning participation and encourage students to adopt environmentally friendly behaviors in their daily lives. This study concludes that the appropriate integration of digital content with Islamic values is a key strategy to ensure environmental education in Islamic schools remains relevant, meaningful, and effective for future generations.